One stage repair for an oesophageal fistula after pneumonectomy using an omental pedicle flap. - Asaoka, M (1988)
A 67 year old man developed an oesophageal fistula after a pneumonectomy that was complicated by an empyema. An omental pedicle flap was brought through the diaphragm to repair the fistula and to fill the empyema space. The outcome was successful.